EXPLORING THE CONCEPT OF REFLECTIVE PRACTICE IN THE CONTEXT OF STUDENT-CENTERED TEACHER EDUCATION - Bubnys, Remigijus; Zavadskienė, Loreta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Being one of the most popular theories of professional knowledge in the last 30 years, reflective practice has been widely adopted not only by practicing teachers in their working environment, but in pre-service teacher education as well. Meeting the need to respond to the challenges posed by the society nowadays, higher education is undergoing radical changes calling for the proper implementation of student-centered studies. In the context of such a paradigm shift there is a strong urge for the concept of reflective practice to be examined more carefully so that it could be put into effect in the studies of higher education. The paper seeks to respond to this problem by offering an in-depth analysis of the attributes characteristic of the concept of reflective practice in the paradigm shift. Based on the thorough review of scientific works dealing with the concept of reflective practice in teacher education, the current study reports on the insights regarding the development of this concept for reflective practice to be successfully applied in the process of teacher education.